Quantitative assessment of the elasticity values of liver with shear wave ultrasonographic elastography - Arda, Kemal (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND & OBJECTIVES: Tissue stiffness in liver is related to tissue composition, which is changed by cirrhosis, hepatocellular carcinoma or metastases. Shear wave ultrasonographic elastography is a new imaging technique by which the elasticity of soft tissue can be measured quantitatively. The aim of this study was to measure the elasticity values of liver segments in healthy volunteers. METHODS: One hundred twenty seven healthy volunteers (89 women, 38 men; mean age 37, 72 ± 9.11 yr, range 17-63 yr) were examined on shear wave elastography and ultrasonography by using convex probe with a frequency of 3 MHz. Individuals with liver hepatosteatosis, cirrhosis, chronic liver disease, or focal liver lesions were excluded from the study. RESULTS: The mean elasticity values of right posterior, right anterior, left medial and left lateral segments of the liver was determined as 4 (±2.2), 3.3 (±2.1), 3.8 (±2.1), and 3.7 (±1.9) kPa for each segments, respectively. There was no significant difference in liver elasticity values between men and women. INTERPRETATION & CONCLUSIONS: In this preliminary study the elasticity values of liver segments were measured by shear wave ultrasonographic elastography in normal healthy volunteers. Further studies, comparing elasticity values of normal and pathologic tissues are needed to detect the diagnostic role of this new technique.